The Analysis of Cyrus Smith as A Hero in Jules Verne’s The Mysterious Island - Khairul Ramadhan, Rachmad Fajri (English Literature Study Program, 2023)
Hero is an individual or a group of people overcoming obstacles and dangers to accomplish some critical or moral missions. They would often receive the favors of one or more people as a kind of side benefit (Cawelti, 1976). In this study, the researcher analyzed Cyrus Smith's character in Jules Verne’s The Mysterious Island to get a comprehensive understanding of the hero's character as well as the efforts the character provided as a hero. This study was a part of literary criticism as the researcher studied and analyzed a literary work using structuralism and Cawelti’s adventure formula (1976). There were four formulas introduced by Cawelti, covering adventure, romance, mystery, and melodrama. However, the researcher chose to specifically apply the adventure formula to analyze the hero character in The Mysterious Island written by Jules Verne. The result of the study showed that Cyrus Smith was an ordinary hero whose characteristics were portrayed through his actions, dialogs, and the author’s narration. The portrayal of the ordinary hero went in line with Cawelti’s definition of ordinary hero, namely someone who had more ability than the others in his group and gained favors from other people. Meanwhile, the efforts to make his friends survive contained providing comfort, obtaining food, making medicine, sharing knowledge, providing safety, and manufacturing tools. As the researcher focused only on Cyrus character in Jules Verne’s The Mysterious Island, the researcher suggested that other researchers analyzed Cyrus character using the same theory, enriching the data of the present study. However, the researcher also suggested future researchers to study other characters in this novel using other literary theories.